Understanding of the meaning of leadership from the perspective of Muslim women academic leaders - Almaki, Samah Hatem; Silong, Abu Daud; Idris, Khairuddin; Abd. Wahat, Nour Wahiza (Mediterranean Center of Social and Educational Research, 2016)
Leadership, as one of most widely discussed and researched issues, has been characterized by a variety of definitions, frameworks, and meaning. Such definitions and notions provide a foundation for developing effective leadership in various organizational environments. This paper discusses the meaning of leadership from the perspective of Muslim women leaders in higher education by using a qualitative method and in-depth interviews from selected participants from University Putra Malaysia and King Abdul-Aziz University. The research attempts to answer questions like: what does leadership mean? How can Muslim women leaders become effective leaders in higher education? Findings of the study indicate that there is no difference between both groups of Muslim women leader in understanding the meaning of leadership. It was also found that leadership is strongly linked with vision and goal setting, accountability, role model, engorgement, and empowerment. Finally, implications are put forward to improve the potentiality of Muslim women leaders in different ways.